Gender Differences in Efficacy and Safety of Direct Oral Anticoagulants in Atrial Fibrillation: Systematic Review and Network Meta-analysis. Issue 11 (November 2018) - Raccah, Bruria Hirsh; Perlman, Amichai; Zwas, Donna R.; Hochberg-Klein, Sarit; Masarwa, Reem; Muszkat, Mordechai; Matok, Ilan
Background: Studies indicate that women with atrial fibrillation (AF) are less likely to receive anticoagulants despite their higher risk of stroke compared with men.Objective : To evaluate whether the efficacy and safety of direct oral anticoagulants (DOACs) differ in women with AF as compared with men. Our secondary aim was to examine gender differences regarding the safety and efficacy of specific DOACs.Data Sources: MEDLINE, EMBASE, Cochrane, and ClinicalTrials.gov were searched through March 2017.Study Selection and Data Extraction: Randomized clinical trials that reported on major bleeding and stroke with DOACs in women and men with AF were included. Meta-analysis and network meta-analysis was performed.Data Synthesis: Five trials met the inclusion criteria. Among 66 389 patients, 37.8% were women. Women treated with DOACs were at higher risk of stroke and systemic embolism compared with men (RR = 1.19; 95% CI = 1.04-1.35; I 2 = 10%) but there was a significantly lower risk of major bleeding in women compared with men (RR = 0.86; 95% CI = 0.78-0.94; I 2 = 0%). Network meta-analyses suggested differences between various DOACs in men and women.Limitations: Patient-level data enabling control for differences in baseline risk and head-to-head comparisons between DOACs were not available.Relevance to Patient Care and Clinical Practice: Undertreatment with DOACs among women cannot be justified.Conclusion: Women treated with DOACs had a lower rate of major bleeding and higher rate of stroke and systemic emboli compared with men. Further investigation of DOACs, including differences between the DOACs in specific populations is warranted.